Exploratory Study on the Accreditation Framework of Dayah Institutions in Aceh: An Examination of Policy, Execution, and Organizational Efficacy - Ilyas, Mukhlisuddin; Marwan, Marwan; Munawar, Munawar; Najmuddin, Najmuddin; Khadafi, Muammar (Idarah (Jurnal Pendidikan dan Kependidikan), 2025)
This exploratory study examines the certification system of dayah (Islamic boarding schools) within Aceh Province as a strategic initiative aimed at improving the quality of Islamic education and reinforcing institutional governance. The study integrates data from contemporary empirical research, pertinent government regulations (Qanun Aceh No. 9/2018 and Pergub No. 64/2019), and the operational procedures of the Badan Akreditasi Dayah Aceh (BADA). Utilizing a comprehensive approach that encompasses literature review, organizational analysis, and policy evaluation, the findings indicate that accreditation serves as a pivotal mechanism for standardizing administrative processes, enhancing accountability, and advancing the professional development of educators. Nevertheless, the implementation of accreditation encounters challenges including limited resource availability, opposition to modernization initiatives, and conflicts between national benchmarks and local cultural traditions. Employing an exploratory qualitative methodology, the study highlights the imperative for a contextualized accreditation framework that harmonizes national quality standards with the cultural identity and autonomy intrinsic to dayahs. The study concludes with a proposed model to optimize accreditation efficacy through participatory governance, incorporation of digital innovations such as the E-SADA system, and adaptive leadership practices in dayah management.